Kepribadian Tokoh Utama Laki-Laki Pada Film Yowis Ben Dan Film Star Syndrome : Kajian Sastra Bandingan - Yasmin Lailah Kamilah; Trie Utari Dewi (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to examine the character personality experienced by the main male characters in the films Yowis Ben and Film Star syndrome using Sigmund Freud's theory. This research method uses a qualitative descriptive method with a literary psychology approach. The results of this research are First, the similarities, namely that they both use the comedy genre and discuss the world of music, the struggle of a soloist or group to achieve their dream of becoming a singer. Second, the difference in personality of the male main character is that Bayu in the film Yowis Ben has a personality that tends more towards the Id aspect. Meanwhile, Jay Adi in Film Star Syndrome has a personality that tends more towards the Ego aspect. Thus, there are differences in the psychology of the male main character in achieving his dream of becoming a singer in the films Yowis Ben and Film Star Syndrome.